Baseline serum phosphatidylcholine plasmalogen concentrations are inversely associated with incident myocardial infarction in patients with mixed peripheral artery disease presentations. (August 2017) - Moxon, Joseph V.; Jones, Rhondda E.; Wong, Gerard; Weir, Jacquelyn M.; Mellett, Natalie A.; Kingwell, Bronwyn A.; Meikle, Peter J.; Golledge, Jonathan
Abstract: Background and aims: Despite current best care, patients with peripheral artery disease (PAD) remain at high risk of myocardial infarction, and biomarkers to more accurately assess cardiovascular risk are needed. This study assessed the relationship between the serum lipidome and incident myocardial infarction in a cohort of PAD patients. Methods: 265 PAD patients were followed up for a median of 23 months, during which 18 people suffered a myocardial infarction. Fasting serum concentrations of 332 lipid species were measured via mass spectrometry and their association with incident myocardial infarction was assessed via Cox regression. Secondary analyses investigated prognostic potential of specific lipid species. Results: Total serum concentrations of alkyl-phosphatidylcholine and alkenylphospatidylcholine (plasmalogen) lipids were inversely associated with incident myocardial infarction after adjusting for multiple testing (hazards ratio (95% confidence intervals): 0.43 (0.24–0.74); p  = 0.032; and 0.28 (0.14–0.56), p  = 0.010, respectively). Specifically, 10 alkenylphosphatidylcholine species and 6 alkyl-phosphatidylcholine species were negatively associated with incident myocardial infarction after adjusting for traditional risk factors and correcting for multiple testing (hazards ratios ranging from 0.07 to 0.51, p  < 0.05). Incorporation of serum phosphatidylcholine plasmalogen species PC(P-40:6) concentration within analyses designed to determine subsequent myocardial infarction incidence led to an improvement in predictive accuracy compared to traditional risk factors alone. Conclusions: Serum concentrations of phosphatidylcholine plasmalogens and alkyl-phosphatidylcholines were negatively associated with incident myocardial infarction and have potential to act as novel prognostic markers in at-risk populations. Highlights: We report a serum lipidomic analysis to identify markers of incident MI in patients with peripheral artery disease (PAD). Serum concentrations of PC(O) and PC(P) lipids showed significant inverse associations with incident MI. The lipid species PC(P-40:6) showed the greatest inverse association with incident MI. Considering novel lipids and traditional risk factors improved prognostication.